Asian Regional Institutions and the Possibilities for Socializing the Behavior of States - Amitav Acharya (Asian Development Bank (ADB), 2011)
Departing from the traditional yardsticks for measuring the performance and effectiveness of regional institutions, this paper proposes a new framework to investigate their effect in the socialization (i.e. internalization of group norms by newcomers) of new members. Called Type III internalization, it represents a middle ground between Type I (i.e. member states simply acting according to group expectations, even if they may not agree with them), and Type II (i.e. states transforming themselves by adopting the interests and identities of the group) internalization. In Type III internalization, states act both instrumentally and normatively. While their interests and values do not change permanently, there is enough change to induce substantially new kinds of cooperative behavior, in trade and security. Type III internalization is non-legalistic and consensual, moving at a pace in which everyone is comfortable, but there is no danger of backtracking. New members moderate their competitive instincts and pursue common objectives. The impact of institutional norms such as "open regionalism" and "cooperative security" transmitted through institutions such as the Association of Southeast Asian Nations (ASEAN), Asia-Pacific Economic Cooperation, and the ASEAN Regional Forum on Viet Nam, India, and the People's Republic of China attests to the existence of a Type III internalization.
hdl:11540/2023
Keywords: F50; F55; 330; Asia; regional institutions; Asian regional institutions; constructivism; socialization; institution-design; multilateralism